PENGARUH DEBT TO EQUITY RATIO, DEBT RATIO, LONG TERM DEBT, LONG TERM DEBT TO EQUITY RATIO, DAN LIQUIDITY TERHADAP PROFITABILITY PADA PERUSAHAAN FARMASI - SATRIYO WIBOWO (Media Bisnis, 2016)
The purpose of this research is to test and analyze empirically the influence of debt to equity ratio, debt ratio, long term debt, long term debt to equity ratio, and liquidity on profitability. The object of this research is pharmaceutical companies that listed in Indonesia Stock Exchange period 2002-2014. The purposive sampling is used as sampling technique, where 8 companies met the criteria and where analyzed using Eviews8 panel data regressions with random effect model to test the hypothesis. The result of this research shows that debt to equity ratio, debt ratio, long term debt, long term debt to equity ratio, and liquidity influence the profitability.